Contours of corporate management models: cases of Ukraine and China - Purtov, Vladimir (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2017)
An important trend in the modern development of the countries with transition economy is the creation of joint-stock companies and improvement of the forms and methods of corporate management. The restructuring of Chinese model of economic development is carried out consequentially in accordance with the developed concept of two systems in one state. China’s experience indicates, that in the XXI-st century it’s necessary to strive not to global universalism, but to preserve the civilizational identity, which allows not to interrupt, but to continue the story under new conditions. In this sense, China’s model of economic development requires careful study to find the ways of fixing the problems of unstable economies of other countries. The paper attempts to identify the main features of corporate management in Ukrainian and Chinese companies on the basis of the current legislation of both countries. Comparative analysis of corporate management models was carried out, using a number of allotted characteristics – participants, activity monitoring, shareholding structure, legislative framework, company’s management structure, information disclosure.